2010
DOI: 10.1093/aler/ahq013
|View full text |Cite
|
Sign up to set email alerts
|

Do Gun Buybacks Save Lives? Evidence from Panel Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…This could include facilitating crossstate comparisons outputs, 23 particularly when there is practice variation or when the timing of legislative changes creates a natural experiment, in a similar manner to recent work on the timing of gun buybacks and the effect on firearm-related suicide. 38 Despite a decade of significant infrastructure support for data linkage and the development of the PHRN, several Australian states appear to have very few research publications involving use of their linked hospital data. The funding breakdown by state indicates that, with the exception of Tasmania, all Australian states received a total of A$5-9.5 million in direct and 'in-kind' funding to support data linkage between the 2011 and 2013 financial years.…”
Section: Discussionmentioning
confidence: 99%
“…This could include facilitating crossstate comparisons outputs, 23 particularly when there is practice variation or when the timing of legislative changes creates a natural experiment, in a similar manner to recent work on the timing of gun buybacks and the effect on firearm-related suicide. 38 Despite a decade of significant infrastructure support for data linkage and the development of the PHRN, several Australian states appear to have very few research publications involving use of their linked hospital data. The funding breakdown by state indicates that, with the exception of Tasmania, all Australian states received a total of A$5-9.5 million in direct and 'in-kind' funding to support data linkage between the 2011 and 2013 financial years.…”
Section: Discussionmentioning
confidence: 99%
“…This result can explain why many studies show small or negligible effects from gun control in the United States (e.g. Ludwig and Cook, 2000) but others show more substantial effects from very large restrictions on gun ownership such as occurred, for example, in Australia (Leigh and Neill, 2010). The fact that gun control may only be effective when it results in very large decreases in gun ownership suggests that there may be no way of squaring the trade-off noted in the introduction between gun ownership by law-abiding hunters and other gun enthusiasts and potentially opportunistic suicides.…”
Section: Other Measures Over 2000-2009mentioning
confidence: 99%
“…On the other hand, policy change studies have shown that decreased access to firearms can decrease suicide overall. In one careful study, Leigh and Neill (2010) find that the mandatory buyback of 20% of the stock of firearms in Australia in 1997 (which halved the number of households holding firearms) led to nearly an 80% reduction in suicides. Similarly, Lubin et al (2010) show that when drafted soldiers in the Israeli military were prohibited from bringing their guns home with them for the weekend, suicide fell by 40%, owing to a fall in suicides over weekends that was not accompanied by an increase in weekday suicides.…”
Section: Introductionmentioning
confidence: 99%
“…Political scientists, legal scholars, criminologists, economists and scientists working in medical fields all added their voices to the discussion. From my perspective, the most noteworthy (for data and methods used, as well as results) econometric studies on guns and crime appearing after Lott and Mustard (1997) include Ludwig (1998);Duggan (2001); Leenaars and Lester (2001); Cook andLudwig (2003, 2006); Cook et al (2007) and Leigh and Neill (2010). Some works in this area bear strongly worded titles that rather clearly reflect their authors' perspectives: "Shooting Down More Guns, Less Crime" (Ayres and Donohue 2003b), "The Final Bullet in the Body of the More Guns Less Crime Hypothesis" (Donohue 2003) and "The Latest Misfires in Support of the More Guns, Less Crime Hypothesis" (Ayres and Donohue 2003a).…”
Section: Introduction ½ áòøöó ù ø óòmentioning
confidence: 99%